Investigation of entropy generation and natural convection in a trapezoidal porous enclosure with a square hole: A finite element analysis - Amir Mohammad Mirzaei; Mohammad Mokhtari Mehmandoosti; Mohamad Ali Bijarchi; Davood Domiri Ganji (Case Studies in Thermal Engineering)
Natural convection heat transfer within porous media plays a crucial role in improving energy efficiency and addressing various industrial challenges. This study examines natural convection and entropy generation within a trapezoidal porous enclosure with a square hole, considering the effects of dissipation and thermal radiation. The objective is to identify optimal conditions that improve energy efficiency while reducing irreversibility in terms of entropy generation. The finite element method (FEM) is utilized for numerical simulation, and validation against experimental data ensures accuracy. The analysis was conducted on various parameters spanning wide ranges, including Rayleigh number (104–106), radiation parameter (0–5), inverse Darcy number (0–200), Forchheimer resistance (0–7.5), Prandtl number (0.1–10), and aspect ratio (0–0.6). The effects of these parameters on heat transfer, flow patterns, and entropy generation were analyzed. The findings suggest that an increase in Rayleigh number intensifies buoyancy effects, leading to higher entropy generation and modified temperature distribution. Although radiation alteration directly influences heat transfer, its increment notably reduces system irreversibility. In addition, an increment in the inverse Darcy number results in reduced permeability, which restricts fluid flow and decreases both heat transfer and entropy generation.